Macroinvertebrate communities of karst springs in the Julian Alps in relation to environmental factors - Nataša Mori (Natura Sloveniae)
Karst springs in the Julian Alps were investigated from May to September 1999 to examine the influence of physical and chemical characteristics on macroinvertebrate community composition. The study revealed a great heterogeneity of environmental characteristics and highly variable taxonomic composition and abundance of taxa among individual springs. The results of canonical correspondence analysis (CCA) showed that spring altitude and periphyton coverage were the only environmental parameters significantly influencing the macroinvertebrate community composition.